CRISPRa‐based activation of Fgf21 and Fndc5 ameliorates obesity by promoting adipocytes browning - Hongtao Zhu; Dan Liu; Ming Sui; Meiling Zhou; Beibei Wang; Qinqin Qi; Ting Wang; Guo Zhang; Feng Wan; Bin Zhang (Clinical and Translational Medicine, 2023)
Abstract Background Skeletal muscle‐secreted myokines widely participate in lipids metabolism through autocrine, paracrine and endocrine actions. The myokines represented by FGF21 and Irisin can promote the browning of adipocytes and serve as promising targets for treating obesity. Although recombinant myokines replacement therapy and AAV (adeno‐associated virus)‐based myokines overexpression have shown a definite effect in ameliorating obesity, novel myokine activation strategies with higher efficacy and safety are still in pressing need. This study aimed to evaluate the therapeutic potential of a novel CRISPR‐based myokines activation strategy in obesity treatments. Methods In this study, we used lentivirus and a single AAV vector containing dCas9‐VP64 with a single‐guide RNA to selectively activate Fgf21 and Fndc5 expression in skeletal muscles both in vitro and in vivo. The activation efficacy of the CRISPRa system was determined by qRT‐PCR, Western blotting and ELISA. The treatment effect of CRISPR‐based myokines activation was tested in 3T3‐L1‐derived adipocytes and diet‐induced obese (DIO) mice (male C57BL/6 mice, induced at 6‐week‐old for 10 weeks). Results The virus upregulates myokines expression in both mRNA and protein levels of muscle cells in vitro and in vivo. Myokines secreted by muscle cells promoted browning of 3T3‐L1‐derived adipocytes. In vivo activation of myokines by AAVs can reduce body weight and fat mass, increase the adipocytes browning and improve glucose tolerance and insulin sensitivity in DIO mice. Conclusions Our study provides a novel CRISPR‐based myokines activation strategy that can ameliorate obesity by promoting adipocytes browning.